2021
DOI: 10.1186/s12885-021-09031-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of mucinous component in colorectal adenocarcinoma: a propensity score-matched study

Abstract: Background This study aims to investigate the clinical significance and prognostic value of mucinous component (MC) in colorectal adenocarcinoma (AC). Methods Patients with colorectal AC and AC with MC (ACMC) (1–100%) underwent surgical resection between January 2007 and February 2018 were retrospectively reviewed. Propensity score matching (PSM) was performed according to a 1:1 ratio. Receiver-operating characteristic (ROC) curve was used to ident… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 35 publications
(46 reference statements)
2
11
1
Order By: Relevance
“…The present study showed that chemotherapy is a protective factor for CRMA patients, suggesting that CRMA patients can benefit from chemotherapy. Therefore, chemotherapy is still effect of mucin on survival may be associated with its proportion in the lesion, and mucous component >70% may serve as a biomarker for poor prognosis [44]. We found that OS has a lower predictive accuracy than CSS because of the competitive risk.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…The present study showed that chemotherapy is a protective factor for CRMA patients, suggesting that CRMA patients can benefit from chemotherapy. Therefore, chemotherapy is still effect of mucin on survival may be associated with its proportion in the lesion, and mucous component >70% may serve as a biomarker for poor prognosis [44]. We found that OS has a lower predictive accuracy than CSS because of the competitive risk.…”
Section: Discussionmentioning
confidence: 74%
“…SUMA et al reported that the percentage of mucus components was significantly associated with tumor aggressive behavior and poor prognosis in colorectal mucinous adenocarcinoma [ 43 ]. What is more, Yan et al reported that the effect of mucin on survival may be associated with its proportion in the lesion, and mucous component >70% may serve as a biomarker for poor prognosis [ 44 ]. We found that OS has a lower predictive accuracy than CSS because of the competitive risk.…”
Section: Discussionmentioning
confidence: 99%
“…Rectal mucinous adenocarcinoma (RMA) is a distinct pathological subtype of rectal cancer, characterized by the presence of extracellular mucinous components comprising more than 50% of the tumor volume ( 3 ). Numerous studies have indicated that RMA is associated with poor prognosis ( 4 , 5 ), which is closely associated with a higher proportion of lymph node infiltration, peritoneal implantation, and larger tumor volumes ( 6 , 7 ). Nonetheless, the treatment strategies for RMA and rectal cancer are similar, advocating for neoadjuvant chemoradiation (NCR) before total mesorectal excision (TME) surgery, followed by standard adjuvant chemotherapy (AC) ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In colorectal MAC, MUC1 and MUC13 are transmembrane mucins, while MUC2 and MUC5AC are secreted gell-forming mucins resistant to tumor cell death and form an immune infiltrating barrier [ 12 ]. In comparison to non-mucinous adenocarcinoma (NMAC), MAC is more common in women, and it has more advanced T or N stage, proximal location, worse differentiation, and a higher ratio of peritoneal implant, microsatellite instability-H (MSI-H) or BRAF mutation [ 15 18 ]. Due to the inherent characteristics of MAC, it often responds poorly to conventional therapy [ 14 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%